Endoscopic colloid cyst resection by puncture of the medial wall of lateral ventricle, posterior to the foramen of Monro - D. Păunescu; M. Gorgan; Ligia Tătăranu (Romanian Neurosurgery, 2012)
No consensus among neurosurgeons has been reached so far concerning optimal therapeutic strategy for colloids cysts, especially as these are non-invasive,slow-growing, benign lesions. In symptomatic cases, endoscopic resection can be achieved as first intention when it seems to have a cyst containing fluid and there is ventriculomegaly. Cyst location and degree of superior distension of the third ventricle roof, associated with the emergence of Monro’s foramen can cause problems when using a rigid endoscope, the visualisation being impossible or difficult. Posterior interventricular foramen puncture may be helpful in such cases.